Novel anterior curved incision combined with MIPO for Pilon fracture treatment - Dankai Wu; Chuangang Peng; Guangkai Ren; Baoming Yuan; He Liu (BMC Musculoskeletal Disorders, 2020)
Abstract Backgrounds Poor prognosis was reported for complex Pilon fractures involving severe soft tissue damage. It is therefore useful to explore the evolution of different treatment strategies in an effort to reconstruct the axial alignment and articular surface, while minimizing additional damage to the surrounding soft tissues. Methods Seventeen patients with Pilon fractures were enrolled in this retrospective study from December 2009 to October 2014. The injuries were graded according to AO Classification and the Gustilo-Anderson system. Patients were treated with minimally invasive plate osteosynthesis (MIPO) combined with curved incision on the anterior area of ankle. The ankle function and radiological outcome were assessed by the modified Mazur ankle score and Burwell-Charnley criteria, respectively. Visual analogue score (VAS) score was used to assess the degree of patient’s ankle pain, and related complications were also recorded. Results The mean time for fracture healing was 3.6 months (range: 3–6 months). According to Mazur’s criteria, surgical treatment achieved good or excellent outcome in 15 (88.2%) cases, and the average VAS score was 1.19 ± 0.52. On the basis of Burwell-Charnley score, 12 (70.5%) patients achieved anatomic recovery, 4 (23.5%) obtained good reduction, and only 1 (5.9%) patient was diagnosed with valgus deformity. Additionally, 1 (5.9%) patient developed a superficial infection around incision, and 2 (11.8%) experienced superficial peroneal nerve damage. In addition, 2 (11.8%) patients showed radiographic evidence of existing ankle osteoarthritis at the final follow-up. Conclusions This retrospective study is the first to assess the application of a curved incision on the anterior area of ankle with MIPO for the treatment of Pilon fractures, which achieves high functional recovery with a low complication rate. However, large randomized controlled trials comparing different approaches and fixation methods are still needed to conclusively identify the optimal treatment protocol.